Self‐retaining barbed suture for parenchymal repair during laparoscopic partial nephrectomy; initial clinical experience - Olweny, Ephrem O.; Park, Samuel K.; Seideman, Casey A.; Best, Sara L.; Cadeddu, Jeffrey A. (BJU international, 2012)
Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? This paper reports on outcomes for SRBS during conventional laparoscopic partial nephrectomy. In addition to an improvement in warm ischaemia time, we found that SRBS use during LPN may be beneficial in reducing rates of clinically significant haemorrhage. OBJECTIVES • To evaluate the efficacy of a self‐retaining barbed suture (SRBS) in achieving a secure and haemostatic renorrhaphy during laparoscopic partial nephrectomy (LPN). • To compare perioperative outcomes for LPN with SRBS with those for LPN with conventional polyglactin suture, with specific attention to warm ischaemia time, blood loss and need for postoperative bleeding interventions. PATIENTS AND METHODS • Patients who underwent LPN between June 2007 and October 2010 were identified through an Institutional Review Board approved registry of oncological patients. • Before July 2009, parenchymal repair after tumour excision was performed using absorbable polyglactin suture (Group 1), and subsequently, using SRBS (Group 2). • Demographic, clinical, intraoperative and postoperative outcomes were compared for each group. RESULTS • LPN was performed in 49 patients in Group 1 and 29 in Group 2. • Baseline demographic and clinical features, estimated blood loss, and transfusion and embolization rates were statistically similar for the cohorts. • Mean warm ischaemia time (±SD) was significantly shorter for the SRBS group (26.4 ± 8.3 vs 32.8 ± 7.9; P= 0.0013). • Bleeding requiring intervention (open conversion or transfusion ± embolization) was more common for Group 1 (9/49, 18.4% vs 1/29, 3.4%; P= 0.06). CONCLUSIONS • The use of SRBS for parenchymal repair during LPN in humans is safe and is associated with a significant reduction in warm ischaemia time. • SRBS use during LPN may also reduce rates of clinically significant bleeding. • Prospective, larger studies to confirm the value of SRBS use in minimally invasive partial nephrectomy are warranted.